GROUND OF PARAMETERS OF REDUCING GEAR OF DEVICE FOR LIQUIDATION OF FAILURES OF PIPES IN MINING HOLE - Гаврилів, Світлана Юріївна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The scheme of planetary gear unit device for unscrewing pipes have been considered. On the basis of the strength toothing calculations optimization expediency of gear unit geometrical parameters have been developed. The criteria optimization have been determined. The theoretical dependence of optimization parameters of the gear unit depending on the gears width have been received. It is planned to manufacture planetary gearbox with optimal size.